Deteksi Cemaran Bakteri Escherichia coli dalam Jaruk Tigaron pada Pasar Sungai Andai dan Pasar Lama Kota Banjarmasin - Ika Oksi Susilawati; Rini Saidah (BIO-SITE |Biologi dan Sains Terapan, 2018)
Jaruk tigaron is one of the traditional fermented foods originating from South Kalimantan made by fermented tigaron flowers (Crataeva nurvala, Buch HAM). The process of making traditionally allows contamination by the bacteria Eschericia coli (E.coli). Escherichia coli is the most commonly used a microbe as an indicator of faecal contamination in water, even food or beverages, including various types of jaruk. This final project aims to detect Escherichia coli on jaruk tigaron thatdistributed in Banjarmasin. The method was used in detecting Escherichia coli is the Most Probable Number (MPN) with five test stages are estimation test, confirmatory test, complementary test, biochemical test (TSIA and IMVIC). The media was used is a Lactose Broth Single Strength (LBSS) by 3 series for forecasting test, Brilliant Green Bile Broth (BGLB) media for confirmatory test, Eosin Methylene Blue Agar (EMBA) media for complementary test, TSIA test and IMVIC test. The test results was obtained by MPN index on samples (a) 28 samples (b)> 1.100 and sample (c) 20. The detection results is Escherichia coli on jaruk tigaron thatdistributed in Banjarmasin declared negatively containing Escherichia coli but only contain Coliform bacteria. Based on SNI 7388: 2009, the determination of the maximum limit of microbial contamination in food is the absence of Coliform and Escherichia coli bacteria in 100 ml of sample